2021
DOI: 10.1093/brain/awab307
|View full text |Cite
|
Sign up to set email alerts
|

Dimethyl fumarate treatment restrains the antioxidative capacity of T cells to control autoimmunity

Abstract: Dimethyl fumarate, an approved treatment for relapsing-remitting multiple sclerosis, exerts pleiotropic effects on immune cells as well as CNS resident cells. Here, we show that dimethyl fumarate exerts a profound alteration of the metabolic profile of human CD4 + as well as CD8 + T cells and restricts their antioxidative capacities by decreasing intracellular levels of the reactive oxygen species scavenger glutathione. This causes an increase in mitocho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 60 publications
1
16
0
Order By: Relevance
“…Seahorse Extracellular Flux analysis was performed according to the manufacturer’s protocol as described [ 18 , 19 ]. Briefly, cells in appropriate numbers were seeded in Poly-D-Lysine (Sigma-Aldrich, Darmstadt, Germany) coated XFe96 plates (Agilent Technologies, North Billerica, MA, USA) in the XF DMEM medium with optimized concentrations of supplements.…”
Section: Methodsmentioning
confidence: 99%
“…Seahorse Extracellular Flux analysis was performed according to the manufacturer’s protocol as described [ 18 , 19 ]. Briefly, cells in appropriate numbers were seeded in Poly-D-Lysine (Sigma-Aldrich, Darmstadt, Germany) coated XFe96 plates (Agilent Technologies, North Billerica, MA, USA) in the XF DMEM medium with optimized concentrations of supplements.…”
Section: Methodsmentioning
confidence: 99%
“…Nrf2 activators have been extensively applied in clinical research, among which sulforaphane, synthetic triterpenoids, and dimethyl fumarate are the most successful examples. 184 , 411 In preclinical studies, these three compounds were widely reported to function in many disease situations including type 2 diabetes, 425 epilepsy, 426 pachyonychia congenita, 427 cancers, 428 , 429 , 430 autoimmunity, 431 AD, 432 and infections. 433 A large number of clinical trials are currently being carried out in patients with a range of disorders, some of which have undergone preliminary tests and some have even been approved (NCT01335971, NCT03517995, NCT00322140, NCT02683863).…”
Section: Therapeutic Implications Of Rewiring the Redox Statementioning
confidence: 99%
“…In this context, recent publications 2–6 set a spotlight on dimethyl fumarate (DMF), a frequently administered DMT. DMF is a bona fide immunometabolic compound with metabolic properties on the mitochondrial respiration of activated T cells 5 and restrictive effects on glycolysis in lymphocytes. 2 , 6 Yet, it is likely that the effects of this empirically developed, untargeted, small molecule reach beyond T cells, potentially affecting other metabolically active human and bacterial cells.…”
Section: Introductionmentioning
confidence: 99%